A System Integration Analysis of a Molten Carbonate Electrolysis Cell as an Off-Gas Recovery System in a Steam-Reforming Process of an Oil Refinery - Monforti Ferrario, Andrea; Santoni, Francesca; Della Pietra, Massimiliano; Rossi, Mosè; Piacente, Nicola; Comodi, Gabriele; Simonetti, Luca (Frontiers in Energy Research, 2021)
Technologies capable of efficiently exploiting unavoidable CO2 streams, have to be deeply investigated and deployed during the transition phase to achieve long-term climate neutrality targets. Among the technologies, Molten Carbonate Cells (MCC) Operating in Electrolysis Mode (MCEC) represents a promising facility to valorize CO2-rich waste streams, which are typically available in industrial plants, by their conversion into a high-value H2/CO syngas. These gaseous products can be reintegrated in a plant or reused in different applications. This study analyzes the integration of a system of the MCEC unit under different operating conditions in terms of composition, current density, and the utilization of fuels in a steam-reforming process of an Italian oil refinery via a mixed experimental-simulative approach. The aim of the current study is to assess the improvement in the overall product yield and further impacts of the MCEC unit on the plant efficiency. The results have shown that it is possible to obtain an electrochemical Specific Energy Consumption for the production of H2 of 3.24 kWh/NmH23 using the MCEC, whereby the possible integration of a 1-MWe module with a reformer of the proposed plant not only increases the hydrogen yield but also decreases the amount of fuel needed to assist the reforming reaction and separates a CO2 stream after additional purification via an oxy-fuel combustor, consequently determining lower greenhouse gases emissions.